Next generation L2-based HPV vaccines cross-protect against cutaneous papillomavirus infection and tumor development - Ahmels, Melinda; Mariz, Filipe C.; Braspenning-Wesch, Ilona; Stephan, Sonja; Huber, Bettina; Schmidt, Gabriele; Cao, Rui; Müller, Martin; Kirnbauer, Reinhard; Rösl, Frank; Hasche, Daniel (Frontiers in Immunology, 2022)
Licensed L1-VLP-based immunizations against high-risk mucosal human papillomavirus (HPV) types have been a great success in reducing anogenital cancers although they are limited in their cross-protection against HPV types not covered by the vaccine. Further, their utility in protection against cutaneous HPV types, of which some contribute to non-melanoma skin cancer (NMSC) development, is rather low. Next generation vaccines achieve broadly cross-protective immunity against highly conserved sequences of L2. In this exploratory study, we tested two novel HPV vaccine candidates, HPV16 RG1-VLP and CUT-PANHPVAX, in the preclinical natural infection model Mastomys coucha. After immunization with either vaccines, a mock control or MnPV L1-VLPs, the animals were experimentally infected and monitored. Besides vaccine-specific seroconversion against HPV L2 peptides, the animals also developed cross-reactive antibodies against the cutaneous Mastomys natalensis papillomavirus (MnPV) L2, which were cross-neutralizing MnPV pseudovirions in vitro. Further, both L2-based vaccines also conferred in vivo protection as the viral loads in plugged hair after experimental infection were lower compared to mock-vaccinated control animals. Importantly, the formation of neutralizing antibodies, whether directed against L1-VLPs or L2, was able to prevent skin tumor formation and even microscopical signs of MnPV infection in the skin. For the first time, our study shows the proof-of-principle of next generation L2-based vaccines even across different PV genera in an infection animal model. It provides fundamental insights into the humoral immunity elicited by L2-based vaccines against PV-induced skin tumors, with important implications to the design of next generation HPV vaccines.